The Application of Thermal Decomposition for Determination of Carbonate Acid-Neutralising Capacity for Improved Acid Mine Drainage Prediction - Andrea R. Gerson (MDPI AG, 2021)
This study developed an industry-applicable, thermal decomposition methodology for quantification of carbonate mineral acid neutralisation capacity (ANCtherm-carb) for waste rock, tailings, and other mined materials. Standard titration-based methods for ANC can be compromised due to contributions from silicate minerals, ion exchange, Fe-rich carbonates, and other transition metal carbonates. C emission (CO2 and CO) was measured using IR in a N2 atmosphere. Cneut (wt%) was calculated using the C emission at 800 or 1000 °C minus the C emission at 400, 450 or 500 °C and the weight of sample prior to decomposition (Equation (2) of this manuscript). This value was then input into Equation (3) of this manuscript to calculate ANCtherm-carb. Good correlation of ANCtherm-carb for single-mineral carbonates with ANCcalc, calculated from bulk assay concentrations for Mg, K, Na, Ca, and Mn, was achieved. Thereafter, 18 waste rock samples were examined, resulting in the correlation of ANCtherm-carb versus non-standard ANCtitrate-carb (titration methodology adapted to focus on carbonate neutralisation only) with R2 = 0.96. This correlation is valid for samples containing both non-neutralising carbonates (siderite) and sources of neutralisation arising from non-carbonates (Mg-clay) within this waste rock system. Typically, mining operations use total C measurements for assessment of carbonate neutralisation potential in the block and mining model. This method provides an effective means to cheaply analyse for carbonate neutralisation potential with assignment of potentially acid-forming and non-acid-forming blocks to waste rock cells, etc.